Synthesis, structural, optical and magnetic properties in the sprayed ZnO: Fe3+: explanations of the origin of the tuned ferromagnetism and optical parameters by first principle. (13th July 2018) - El Haimeur, A; Zarhri, Z; El Gana, L; Zimou, J; Addou, M; Colin, J; El Kenz, A
Abstract: Fe 3+ doped ZnO was elaborated using spray pyrolysis deposition technique with different concentrations of the doping element then characterized by the x-ray diffraction for the structural characterizations of our samples. We investigated optical properties using Uv-Vis spectrophotometer in the wavelength range of 200–880 nm and also magnetic properties by first principal density functional theory electronic structure calculations to estimate the sample magnetic properties and the Curie temperature. The change in the physical parameters and its relation with the measured optical band gap were investigated in detail to understand the cause and to improve the optical and magnetic properties. The measured optical absorption spectra and band gap values are in agreement with the Ferromagnetic stability of the magnetic dopants charge states. The magnetic interaction was explained by the Zener p-d double exchange. The optimized structure was confirmed using the first-principle stability calculations.